(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Ethics committees (ECs) constitute a galaxy of organisms for which different functions and compositions are provided. This contribution focuses on some aspects related to the configuration of the Italian National Bioethics Committee, analysing its functions of mediation-representation and mediation-conciliation. To this end, emphasis will be placed on the criteria chosen for the composition of an organism aimed at reflecting as much as possible the cultural and religious pluralism present in the country. Finally, some reflections will be advanced regarding how the role of a member of the National Bioethics Committee can be interpreted and the delicacy of acting within a public body that aims to seek mediation to achieve the maximum possible consensus. The search for the ideal solution must therefore be reconciled with that of a common, realistic, and practicable position, taking into account the context in which the opinions of a committee like the CNB are read and received.